2017
DOI: 10.1177/0885328217698062
|View full text |Cite
|
Sign up to set email alerts
|

Urinary bladder extracellular matrix hydrogels and matrix-bound vesicles differentially regulate central nervous system neuron viability and axon growth and branching

Abstract: Central nervous system neurons often degenerate after trauma due to the inflammatory innate immune response to injury, which can lead to neuronal cell death, scarring, and permanently lost neurologic function. Extracellular matrix bioscaffolds, derived by decellularizing healthy tissues, have been widely used in both preclinical and clinical studies to promote positive tissue remodeling, including neurogenesis, in numerous tissues, with extracellular matrix from homologous tissues often inducing more positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 91 publications
1
46
0
Order By: Relevance
“…These constructs have the advantage of maintaining tissue‐specific cell functions and phenotypes to induce host tissue remodelling. Previous studies 23–38 have had success in obtaining aECM scaffolds from virtually all mammalian organs. They preserve the native vasculature for adequate perfusion of constructs able to withstand physiological blood pressures, something that has been a challenge to RM methods relying on progenitor cell embryogenesis 39,40 .…”
Section: State‐of‐the‐art Regenerative Medicine Technologiesmentioning
confidence: 99%
“…These constructs have the advantage of maintaining tissue‐specific cell functions and phenotypes to induce host tissue remodelling. Previous studies 23–38 have had success in obtaining aECM scaffolds from virtually all mammalian organs. They preserve the native vasculature for adequate perfusion of constructs able to withstand physiological blood pressures, something that has been a challenge to RM methods relying on progenitor cell embryogenesis 39,40 .…”
Section: State‐of‐the‐art Regenerative Medicine Technologiesmentioning
confidence: 99%
“…The implantation of large segments (>24cm 2 ) of urinary bladder into porcine bladder showed infiltration of smooth muscle cells and promoted angiogenesis after 30 days . Vesicles derived from urinary bladder ECM had a positive effect on neuron neurite growth and on spinal cord injury repair . Urinary bladder‐derived ECM also had a better effect on the treatment of open wounds when compared with conventional therapies .…”
Section: Major Tissues and Organs Used For Decellularizationmentioning
confidence: 98%
“…Urinary bladder has been one of the first organs selected for decellularization. Recent studies on ECM derived from decellularized bladder have indicated a beneficial effect on neuron survival, stem cells, spinal cord, and open wounds . Urinary bladder‐derived ECM has shown greater advantage than cardiac‐derived ECM in remodelling and for attracting site‐specific cells (cardiomyocytes) after implantation .…”
Section: Major Tissues and Organs Used For Decellularizationmentioning
confidence: 99%
See 2 more Smart Citations